An Experimental Investigation into the Association of Traumatic Occlusion with Parodontal Disease: (Section of Odontology) - Stones, H. H. (1938)
(1) The production of traumatic occlusion by inserting raised fillings in the teeth of monkeys is described. The fillings were inserted in three adjoining posterior teeth, one being left higher than the others. In one monkey an upper central incisor was the only tooth treated and on this was fixed a raised metal crown. (2) Experiments were terminated after varying periods of time, from ten to forty-three weeks. The jaws containing the teeth in which raised fillings were inserted, the opposing teeth, and the controls, were sectioned. Some sections were cut mediodistally and others faciolingually. (3) Results. These were judged from a histological examination of the sections.(a) Seven monkeys were treated. (b) In three monkeys very definite changes analogous to parodontal disease were produced. (c) In three monkeys less extreme changes were seen. (d) In one monkey there was no change. (e) in each animal the pathological changes were usually observed in only the one tooth which took the greatest stress of the three that were filled and the opposing one with which it articulated. (f) Of the 39 teeth subjected to trauma eleven showed pathological changes in the subgingival tissues. (4) The clinical evidence in man is considered. (5) The conclusion is reached that traumatic occlusion is an ætiological factor in the production of that variety of parodontal disease in which there is vertical pocket formation associated with one or a varying number of teeth.